Understanding Drug Abuse Patterns in Asia: A Systematic Comparative Review of Community-Level Impacts and Interventions - Tunggal, Deif; Wardani, Nimas Prita Rahajeningtyas Kusuma (Manunggal Halim Jaya, 2025)
This study explores the evolving landscape of drug abuse across Asia and critically examines the role of community-level interventions in addressing substance use disorders within diverse cultural and structural contexts. Employing a qualitative systematic literature review approach, the research synthesizes findings from 75 peer-reviewed articles, institutional reports, and policy briefs published between 2005 and 2024. The study investigates three primary dimensions: emerging epidemiological patterns of drug use, the design and effectiveness of community-based interventions, and the enabling or constraining structural factors that shape public health outcomes. Data analysis was conducted through thematic coding and narrative synthesis, enabling cross-national comparisons and contextual interpretation of intervention frameworks. The findings reveal a significant shift from traditional opioid use in rural and borderland regions to increasing synthetic stimulant and poly-substance use in urban centers, driven by socio-economic stress, youth culture, and digital influences. Community-based interventions that integrate vocational support, mental health counseling, peer mentorship, and cultural components show higher efficacy in relapse prevention and social reintegration. Digital innovations, such as tele-counseling and mobile relapse monitoring, are expanding access, though digital divides remain a concern. Structural enablers, such as health-oriented policies in Malaysia and Vietnam, contrast sharply with punitive frameworks in countries like the Philippines, significantly influencing community trust and intervention sustainability. The study concludes that community-based, multidimensional, and culturally grounded strategies are critical to reducing drug-related harm in Asia and recommends further longitudinal and participatory research to inform equitable policy development..